2022
DOI: 10.21203/rs.3.rs-1448065/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

When the world stops: The impact of COVID-19 on physical activity and physical literacy

Abstract: Matched pre-during pandemic comparison (160 children) revealed a substantial reduction in physical activity (p < 0.001, rrb=0.83), environmental participation (p = 0.046, rrb=0.16), movement valuation (p < 0.001, rrb=0.61), and parent perceptions of children’s physical literacy (p < 0.001, rrb=0.56,). Examining physical activity trajectories, higher pre-pandemic physical literacy protected children from pandemic related activity decline. Emerging from the pandemic, interventions should address childre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…In this study, we observed that the longer the use of electronic products, the higher the risk of a lack of family physical exercise behavior in middle school students. This is consistent with the conclusions of some previous studies ( 28 , 43 ). Schmidt et al reported that during the COVID-19 pandemic, adolescents' total amount of leisure screen time increased significantly, and physical activity decreased significantly.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In this study, we observed that the longer the use of electronic products, the higher the risk of a lack of family physical exercise behavior in middle school students. This is consistent with the conclusions of some previous studies ( 28 , 43 ). Schmidt et al reported that during the COVID-19 pandemic, adolescents' total amount of leisure screen time increased significantly, and physical activity decreased significantly.…”
Section: Discussionsupporting
confidence: 94%
“…And students of different ages have different incidences of not participating in home physical exercise, with the highest proportion of 16-year-old students. A previous study of Chinese adolescents showed that during the COVID-19 pandemic, the prevalence of physically inactive students increased from 21.3 to 65.6% ( 28 ). The reason for this difference from our results may be their physical activity assessment tools (IPAQ–SF), which are different than those used in this research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies should report the deliverer or provider of the intervention and state the topic-related expertise [ 49 ]. This item gains particular relevance in the PL context as differences in the effectiveness across different interventions may be attributed to differing understandings of the concept [ 78 ] and, therefore, to differing implicit intervention foci. Against this background, authors should clarify the disciplinary background (e.g., general pedagogy, physical education, psychology, licensed trainer, kinesiology, physiotherapy, exercise therapy, public health) and skills acquired.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the quality of parental engagement is more impactful than the quantity of their involvement [25]. A survey found 88% of parents felt they had the greatest responsibility for the development of their child's physical literacy [26], which included physical competence. The school is also crucial, as children spend the majority of their time in this setting, and many school divisions have physical education mandates [27].…”
Section: Introductionmentioning
confidence: 99%